Assessing the sources of reionization: a spectroscopic case study of a 30× lensed galaxy at z ∼ 5 with Lyα, C iv, Mg ii, and [Ne iii]. Issue 2 (13th July 2021) - Witstok, Joris; Smit, Renske; Maiolino, Roberto; Curti, Mirko; Laporte, Nicolas; Massey, Richard; Richard, Johan; Swinbank, Mark
ABSTRACT: We present a detailed spectroscopic analysis of a galaxy at z ≃ 4.88 that is, by chance, magnified ∼30× by gravitational lensing. Only three sources at z ≳ 5 are known with such high magnification. This particular source has been shown to exhibit widespread, high equivalent width ${{\rm C\, \small {IV}}}\ \lambda 1549\, \mathring{\rm A}$ emission, implying it is a unique example of a metal-poor galaxy with a hard radiation field, likely representing the galaxy population responsible for cosmic reionization. Using ultraviolet (UV) nebular line ratio diagnostics, Very Large Telescope (VLT)/X-shooter observations rule out strong active galactic nuclei (AGN) activity, indicating a stellar origin of the hard radiation field instead. We present a new detection of ${[{\rm Ne\, \small {III}}]}\ \lambda 3870\, \mathring{\rm A}$ and use the [${\rm Ne\, \small {III}}$ ]/[${\rm O\, \small {II}}$ ] line ratio to constrain the ionization parameter and gas-phase metallicity. Closely related to the commonly used [${\rm O\, \small {III}}$ ]/[${\rm O\, \small {II}}$ ] ratio, our [${\rm Ne\, \small {III}}$ ]/[${\rm O\, \small {II}}$ ] measurement shows this source is similar to local 'Green Pea' galaxies and Lyman-continuum leakers. It furthermore suggests this galaxy is more metal poor than expected from the fundamental metallicity relation, possibly as a consequence of excess gas accretion diluting the metallicity. Finally, we present the highest redshift detection of ${{\rm Mg\, \small {II}}}\ \lambda 2796\, \mathring{\rm A}$, observed at high equivalent width in emission, in contrast to more evolved systems predominantly exhibiting ${\rm Mg\, \small {II}}$ absorption. Strong ${\rm Mg\, \small {II}}$ emission has been observed in most z ∼ 0 Lyman-continuum leakers known and has recently been proposed as an indirect tracer of escaping ionizing radiation. In conclusion, this strongly lensed galaxy, observed just $300\, \mathrm{Myr}$ after reionization ends, enables testing of observational diagnostics proposed to constrain the physical properties of distant galaxies in the James Webb Space Telescope ( JWST )/Extremely Large Telescope (ELT) era.